ATTITUDINAL MEANING IN MARTIN LUTHER KING JR SPEECH: A FUNCTIONAL GRAMMAR APPROACH - Azka Saeful Haq; Lia Maulia Indrayani; Ypsi Soeria Soemantri (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2020)
Racial injustice becomes a primary issue in Martin Luther King Jr’s entitled I have a dream in facing United States social condition. The speech reflects evaluative values to share perspectives toward the issue that can be analyzed by the appraisal system. The use of language certainly constructs different aims in evaluative language, and subjective presence is the target of evaluation in the appraisal system. The subjectivity of Martin Luther King Jr toward racial issues contains various types that can indicate a strategy to persuade people. The objectives of this study are to investigate the evaluative language of Martin Luther King Jr and to infer the meaning of evaluative language use. The strategy of delivering motivational messages is also discussed after acquiring the types of attitudes that will be related to the social issue. The research method employed in this study is descriptive qualitative. Systemic functional linguistic theory pioneered by Halliday and his colleagues becomes the framework in this study, and the tool is an appraisal system pioneered by J.R. Martin to analyze data. There are 90 clauses that consist of 33 judgement, 32 appreciation, and 26 affect. Judgement as the most dominant type reflects the reality of racial injustice to persuade many people to reject the condition. The strategy of critic conveyed in different types of attitudes can share deep messages to many people who listen. The result is hoped to be additional references in revealing speech strategy by using an appraisal system. The study of the appraisal system is useful to observe the subjectivity involvement in every form of language use.